2014
DOI: 10.1016/j.quaint.2013.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the loess/palaeosol sequence in Paks, Hungary: A post-IR IRSL based chronology for the ‘Young Loess Series’

Abstract: In Hungary, many loess/palaeosol sequences have been found to be discontinuous. In order to allow for correlations with other Quaternary records, reliable chronologies are needed. We therefore apply post-IR infrared (IR) stimulated luminescence (post-IR IRSL; pIRIR 290 ) dating to the uppermost 20 m of the loess sequence at Paks. The pIRIR 290 ages are compared with blue quartz OSL ages to test for potential age overestimation due to poor signal re-setting, and the observed good agreement is taken to imply tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
31
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 47 publications
4
31
0
2
Order By: Relevance
“…39 ka) to investigating the variability of sedimentation rates from MIS 3 to the present, and indicate substantial loess accumulation during the last glacial maximum period on the order of 6-8 m within several thousand years . Thiel et al (2014) confirmed previous stratigraphic expectations related to the loess wall in the Paks brickyard, Hungary (Sartori et al, 1999;Horváth, 2001;Marković et al, 2009b;, 2012a (Figure 10). This demonstrates that the loess-palaeosol sequences at Paks are not a continuous record.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…39 ka) to investigating the variability of sedimentation rates from MIS 3 to the present, and indicate substantial loess accumulation during the last glacial maximum period on the order of 6-8 m within several thousand years . Thiel et al (2014) confirmed previous stratigraphic expectations related to the loess wall in the Paks brickyard, Hungary (Sartori et al, 1999;Horváth, 2001;Marković et al, 2009b;, 2012a (Figure 10). This demonstrates that the loess-palaeosol sequences at Paks are not a continuous record.…”
supporting
confidence: 89%
“…This technique, partially developed on European loess, extends the dating range beyond that of quartz, potentially to up to 300 ka (Thiel et al, 2011;Buylaert et al, 2012). This protocol has been successfully applied to a number of Austrian, Hungarian, Croatian, Serbian and Romanian sites, and confirm or extend existing chronostratigraphic models (Schmidt et al, 2010;Thiel et al, 2011Thiel et al, , 2014;…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Still, it is likely that there was significant paleodiversity across the Carpathian Basin, as indicated by diverse loess paleosols suggesting cool-temperate biomes, Frechen et al (1997), Oches and McCoy (1995), Pécsi (1979), Thiel et al (2014), Wintle and Packman (1988) Schatz et al (2011Schatz et al ( , 2012Schatz et al ( , 2014, (2015), Sümegi et al (2007), Sümegi andHertelendi (1998) varying between steppe grasslands (Schatz et al 2011) and forest steppe (Feurdean et al 2014;Kels et al 2014), and their associated ecotones. It is evident that these variations are in part due to complex geographical, geological, climatic and meteorological deviations across both space and time.…”
Section: Environmental Contextmentioning
confidence: 99%
“…За поглядом Пейчі (1986) [25], в Угорщині нема лесу, старшого за 1 млн р, а вік молодих лесів лише 110-130 тис р. На основі нових наукових даних, отри-маних впродовж останніх двох десятиліть, можна стве-рджувати, що леси та палеогрунти Угорщини набагато давніші, ніж вважалося раніше. Грунт MB, що позначає нижню межу молодих лесів, має вік 400 тис р, а утво-рення молодої лесової серії розпочалося перед MIS 9 [28,12,33]. Під час гляціальних фазах в результаті ео-лових процесів формувалася лесова рівнина у західній частині Альфельда (Мезефельд).…”
unclassified